German and euro area economies will benefit from a U.S. interest rate hike in the short term - Max Hanisch (DIW Weekly Report, 2018)
To accompany the economic upturn in the U.S., the Federal Reserve Bank has been raising its benchmark interest rate incrementally. In an increasingly globalized world in which the American economy plays a key role, an action like this has spillover effects on the international level. Based on a dynamic factor model, the present study shows that the member states of the euro area-Germany in particular-can temporarily benefit from a restrictive U.S. monetary policy. The devaluation of the euro against the U.S. dollar will improve the euro area's balance of trade and trigger an economic upturn, primarily in the member states in which the U.S. has captured a substantial portion of exports.
Keywords: C32; E52; E58; 330; spillover; U.S. monetary policy; Eurozone